Los precedentes en nuestro ordenamiento jurídico: su regulación y emisión en materia tributaria - Caller Ferreyros, María Eugenia (2013)
Binding precedents are a tool that not only sustains legal certainty and the right to equality,but also is a unifying path between substantial criteria that is to be applied on similar cases. Even though several jurisdictional bodiesare vested with the power of issuing binding precedents, the lack of specialization in taxmatt ers has enhanced the importance of the binding precedents that the Tax Court issues. The authors highlight the importance of the Tax Court in the development of tax law’s legal framework, thanks to the issuance of binding precedents, as predictability reinforces legal certainty and the right to equality, as well as it reduces the cost of enforcement of tax duties, both for the tax payer and the administration, and has a positive impact on tax collection.